Animated Video-based E-Flashcard Learning Media for Early Childhood Pre-Reading Abilities - Ni Komang Ayu Sari Kresnawati Rena; Made Suarjana; Dewa Gede Firstia Wirabrata (Universitas Pendidikan Ganesha, 2023)
The implementation of flashcards is still focused on image recognition and has yet to go too deep into letter recognition. This research aims to analyse the effect of animated video-based e-flashcards on the pre-reading abilities of young children. This type of research is quantitative with a quasi-experimental method and a non-equivalent control group design. The population of this study was early childhood children from group B class. The research sample consisted of two groups, namely group B1 as the control class and group B3 as the experimental class, totalling 38 children. Data collection methods use observation and documentation. Data analysis techniques use inferential statistics. The research results show the influence of the use of animated video-based e-flashcard learning media on the pre-reading abilities of early childhood. E-flashcard learning media can improve the pre-reading abilities of young children. Animated video-based e-flashcard learning media is equipped with additional features such as animation and sounds that can attract children's attention so that children can focus on the information presented.